No More Sexual Violence - Christsanda, Azzallea Ega Riesta (PCD Journal, 2025)
This study examines how digital platforms are utilised as tools for anti-sexual violence campaigns, with a particular focus on perEMPUan, a woman-led advocacy initiative based on Instagram. By centring the campaign against sexual harassment and violence, this research explores how perEMPUan builds narratives, mobilises public discourse, and fosters collective awareness in digital spaces. Employing a qualitative netnographic approach, the study draws on three main sources: narrative content posted on the Instagram account @_perEMPUan_, audience responses observed in the comment sections, and an in-depth interview with the community’s founder, Rika Rosvianti (also known as Neqy). The findings reveal five thematic categories that reflect the campaign’s core strategies and recurring issues: (1) relationships between public figures and their followers, (2) domestic violence, (3) victim-blaming narratives, (4) the conceptual framing of sexual harassment and violence, and (5) depictions of sexual violence as tragedy. The analysis draws on George and Leidner’s (2019) theoretical framework on the hierarchy of digital activism. The findings point to a distinct division of roles between the advocacy community and its digital audience, particularly in how public discourse around sexual violence is shaped and negotiated in online spaces.